2020
DOI: 10.3390/jmse8030217
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Large Wave Heights from Super Typhoon Nepartak (2016) in the Eastern Waters of Taiwan

Abstract: Super Typhoon Nepartak (2016) was used for this case study because it is the most intense typhoon that made landfall in Taiwan in the past decade. Winds extracted from the Climate Forecast System version 2 (CFSV2) and ERA5 datasets and merged with a parametric typhoon model using two hybrid techniques served as the meteorological conditions for driving a coupled wave-circulation model. The computed significant wave heights were compared with the observations recorded at three wave buoys in the eastern waters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 47 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…A fine mesh with a resolution of approximately 200 m was distributed along the coast of Taiwan (as shown in Figure 2b) and its offshore islands (as shown in Figure 2c), while a coarse mesh with a resolution of approximately 40 km was configured in the open ocean far from the coastal zone. The fine mesh developed in the present study is able to characterize the surf zones and shallow waters [46,[48][49][50][51]. Notably, the performance of the JONSWAP spectrum in the simulation of long-term or extreme sea states in the offshore waters of Taiwan was impressive, and this spectrum has been widely used to simulate wave conditions worldwide [35][36][37][38][46][47][48]52], although the JONSWAP spectrum was originally applied in the North Sea.…”
Section: Description and Configuration Of Schism-wwm-iiimentioning
confidence: 96%
See 1 more Smart Citation
“…A fine mesh with a resolution of approximately 200 m was distributed along the coast of Taiwan (as shown in Figure 2b) and its offshore islands (as shown in Figure 2c), while a coarse mesh with a resolution of approximately 40 km was configured in the open ocean far from the coastal zone. The fine mesh developed in the present study is able to characterize the surf zones and shallow waters [46,[48][49][50][51]. Notably, the performance of the JONSWAP spectrum in the simulation of long-term or extreme sea states in the offshore waters of Taiwan was impressive, and this spectrum has been widely used to simulate wave conditions worldwide [35][36][37][38][46][47][48]52], although the JONSWAP spectrum was originally applied in the North Sea.…”
Section: Description and Configuration Of Schism-wwm-iiimentioning
confidence: 96%
“…Details on the coupling procedure for the SCHISM-WWM-III coupled modeling system are available in [45]. Due to its high numerical efficiency and robust matrix solver, SCHISM-WWM-III has been successfully implemented to investigate wave power resources and produce potential storm wave hazard maps for Taiwan [35,36], evaluate the wind forcing effect on storm wave hindcasting [37], quantify storm tide-induced nonlinear interactions [38], simulate extreme waves caused by a super typhoon [46,47], and evaluate wave-current interactions [48].…”
Section: Description and Configuration Of Schism-wwm-iiimentioning
confidence: 99%
“…Many previous studies have indicated that reanalysis products underestimate typhoon wind speeds, especially for the far-field regions of typhoons [37][38][39][40][41][42]. The peak typhoon wind speed can be considerably improved through a superposition method by combining parametric typhoon and reanalysis winds.…”
Section: Modified Era5 Wind Forcingmentioning
confidence: 99%
“…Typhoons are intensive ocean forces that can destroy coastal properties or offshore engineering structures, leading to significant economic losses [2]. Generally, typhooninduced waves are characterized by extreme heights [3,4], which pose a substantial threat to the stability and structural integrity of floating foundations [5][6][7].…”
Section: Introductionmentioning
confidence: 99%